2015
DOI: 10.1111/jam.12814
|View full text |Cite
|
Sign up to set email alerts
|

Comparative accessory gene fingerprinting of surface water Escherichia coli reveals genetically diverse naturalized population

Abstract: Accessory gene fingerprinting may have important practical implications for improving the specificity of methods that are widely used for quantifying and identifying the sources of faecal contamination in surface water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…Naturalized strains of E. coli have been identified in various water sources (68), but to date, evidence for the presence of naturalized strains of E. coli in a wastewater environment has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Naturalized strains of E. coli have been identified in various water sources (68), but to date, evidence for the presence of naturalized strains of E. coli in a wastewater environment has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, naturalized strains of E. coli have been described for sand, sediment, and water (59), and as such, it may be presumptuous to assume that all E. coli strains observed in wastewater are of fecal origin, creating some authenticity to the emerging yet controversial concept that naturalized strains of E.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Tymensen et al . ). These populations have been reported in sand, soil and sediments as well as in association with macrophytic algae and periphyton (Ishii and Sadowsky ; Sadowsky and Whitman ).…”
Section: Survival and Growth Of Escherichia Coli In Natural Environmentmentioning
confidence: 97%
“…It has been generally assumed that this bacterium is restricted to the gastrointestinal system of warm-blooded animals, but several studies have found that E. coli can survive and replicate outside the gastrointestinal tract of animals in a non-host environment (water/sand/sediment) (Anderson et al, 2005;Byappanahalli et al, 2012;Chandrasekaran et al, 2015;Kon et al, 2007;Power et al, 2005;Solo-Gabriele et al, 2000;Tymensen et al, 2015;Winfield and Groisman, 2003). Survival and colonisation in both the animal host and non-host habitats are mediated by adaptations to nutrient availability, temperature, pH, osmolarity and the presence of competitive microflora.…”
Section: Introductionmentioning
confidence: 99%